KEMAMPUAN MENGERJAKAN SOAL FISIKA MELALUI KONSEP MATEMATIKA AWAL PROSES PEMBELAJARAN FISIKA - Sinta Dewi Tulende; Heinrich Taunaumang; Aswin Hermanus Mondolang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
In general basic laws in physical theory are expressed in mathematical language. Mathematical knowledge is an important prerequisite as initial knowledge that students must possess before studying physics. The purpose of this research is to know and improve students abilities in doing physics problems by using the application of mathematical concepts in the beginning of physics learning. This research is a quantitative descriptive study with test and interview methods. The results of the application of mathematical concepts can improve the ability of students of SMP Negeri 3 Tagulandang in working on physics problems especially on straight motion material. The types of questions used for test are questions that belong to the C1-C6 domain with the highest ability improvement found in C4 questions.